Pengaruh Financing to Deposit Ratio (FDR), Dana Pihak Ketiga (DPK) dan Capital Adequacy Ratio (CAR) Terhadap Pembiayaan Musyarakah: (Studi empiris Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan 2019-2022) - Wijaya, Aldi Teguh; Lie, Janiman (JUDICIOUS, 2024)
Musyarakah financing is one of the profit-loss sharing financing agreements at Islamic Commercial Banks. Where the Distribution of Musyarakah Financing is one of the core products at Islamic Commercial Banks which can begin to compete with Financing products with Sale Purchase or Murabahah contracts. This study aims to analyze the effect of the Financing to Deposit Ratio (FDR), Third Party Funds (DPK) and Capital Adequacy Ratio (CAR) on Musyarakah Financing at Islamic Commercial Banks registered at OJK for the 2019-2022 period. This research is a type of Quantitative Research with research methods used using descriptive analysis methods and classical assumptions consisting of the Normality Test, Multicolonearity Test, Heteroscedasticity Test and Autocorrelation Test. Data analysis techniques using Multiple Regression Analysis, T Test and Coefficient of Determination Test (R2). The population in this study The population in this study totaled 13 Islamic Banks from 2019-2022 with a total sample of 10 Islamic Banks with 4 years of research, so that 40 sample data were obtained. The sampling technique uses purposive sampling. The secondary data used is the annual financial report data from each bank which is published through their respective websites. The results of the study show that the Financing to Deposit Ratio (FDR), Third Party Funds (DPK) and Capital Adequacy Ratio (CAR) variables partially affect Musyarakah Financing.